O treino em psicoterapia na residência de psiquiatria: uma visão da psicologia analítica - Biscaro, Regina Alvares (2008)
With that advance of neurosciences and psychopharmacology, psychiatry has come to great transformations, as in human being conception and as in teaching and education in medical residency. This brought an important advancement in the treatment of mental disorders, but on the other hand, the teaching of psychotherapy decreased its importance, becoming part of an ancient strategy due to the lack of advancement in psychopharmacology. Recent studies though, have retaken the importance of psychotherapy as a strategy of treatment for modifying brain circuits, anciently thought to be only privilege of medication. These discoveries have modified the vision of psychotherapy´s training into psychiatry, showing its importance. Some international works focus on the resident´s training in acquisition of skills in psychotherapy, but this necessity is questionable. The objective of this study was to evaluate a group of residents´ change of consciousness during a training of psychotherapy. A Coortes study was done and a semi-structured questionnaire was used in three moments of the training and also a semi-structured interview at the end. After the results´ evaluation and data debate, it was concluded that the residents have come to transformations during the psychiatric residency period and that the training in psychodynamic psychotherapy provides a deep transformation that even propitiating the arrival of defenses, it contributes to an important change of the resident´s consciousness in relation to one self and in relation to the patient. This transformation provides an empathic listening, a larger symbolic comprehension of symptoms and motivations and the knowledge of oneself, making the resident know a little more about the other and himself in the relationship with the patient, becoming a more humane psychiatrist with a broad approach